Financial Statements in Accordance with IFRS 16 for Leases in the Context of COVID 19 - Polo , Orlando Carmelo Castellanos; Ochoa, Jose Alexander Velasquez; Acosta, Juan Carlos Cardona (International Journal of Membrane Science and Technology, 2023)
This article determines the effects of applying the new requirements of the International Financial Reporting Standard, IFRS 16 on leases, proposed by the International Accounting Standards Board (IASB) and the Financial Accounting Standards Council (FASB), Regarding the correct preparation of the explanatory notes of the complete set of the financial statements of the companies generated with the new amendments to the International Financial Reporting Standards (IFRS), in turn, the EBITDA indicator (’Earnings Before Interests’) was analyzed. , Tax, Depreciation and Amortization’) that shows the gross operating profit before deducting financial expenses. It is the gross operating result, before interest, taxes, depreciation and amortization, whose purpose is to evaluate the behavior and financial situation of companies and the key issues of the Audit report, the effects on a case of a company listed on the stock exchange and the review of 900 Spanish companies from 2019 to 2021, on the profitability indicator (EBITDA) demonstrating by a mixed study, that the guidelines of the regulators caused in the company accelerated processes for its implementation and understanding of the new dynamics that are required in a changing world in the presentation of financial statements . Among the results obtained, it is highlighted that the financial indicators of the companies suffered a lethal impact in the change of IFRS 16 for leases, due to the variations of the items of the financial situation and presentation in the disclosures the uniformity of the information with the previous periods, within the factors the increase in assets, increase in liabilities, and decrease in operating expenses stand out, influencing directly between the indicators that users take into account for their analysis. It is concluded that for the group of companies that did not undergo significant changes were those that had previously classified leases as financial, lease contracts previously classified as operating, if there were significant changes.